(untitled) (Fiep Bulletin - online, 2025)
Introduction: The “Sport in 3 Times” project is a public policy that, through sport, permeates social inclusion in vulnerable environments in the State of Ceará. This works and becomes possible from resources from the Civil House, the state government. In the context of social projects, where resources are often limited and the demand for positive results is high, the adoption of technological tools can represent a crucial differential. Objective: This experience report intends to present the different technologies available for the development and control of pedagogical actions of the social sports project Sport in 3 Times, highlighting their functionalities, benefits and challenges to be conquered. Methods: In the present study, a descriptive narrative was used, focusing on the authors’ experiences through verification and analysis of the system and administrative data of the Sport in 3 Times project. Results: The use of information systems and new technologies can provide interaction, structuring and execution of effective and efficient actions as well as generate equity and democratization in social public policies. Conclusion: The experiences presented can reaffirm the critical importance of information systems and new technologies for the interaction, dynamization, development and effective control of social sports projects.